Work-Related Musculoskeletal Disorders 2019
DOI: 10.5772/intechopen.80303
|View full text |Cite
|
Sign up to set email alerts
|

How Poor Workstation Design Causes Musculoskeletal Disorders: Research from QOC Matrix the Workers’ Voice

Abstract: An ergonomic intervention method based on QOC Matrix the workers' voice was implemented in a study case. The diagnosis and analysis developed are used in improvement proposals for workstation redesign. The workers' voice resulting from reports of the employee' complaints and symptomatology was the base for a standardized method that comprises: (a) QOC questionnaire application, (b) risk factor categorization, (c) determination of unsafe and unhealthy ergonomic metrics, (d) figuring out the task content impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, HBW can also present a number of health challenges for workers. For example, physical issues that can arise from problematic home-based office set-ups, including poor postural habits that lead to musculoskeletal conditions, have been identified (Moretti et al, 2020;Sesenes et al, 2018). Psychosocial issues are also common, and include increased feelings of isolation, decreased work-life balance, loss of motivation, and increases in stress and anxiety (Bellmann & Hübler, 2020).…”
Section: Working From Homementioning
confidence: 99%
“…On the other hand, HBW can also present a number of health challenges for workers. For example, physical issues that can arise from problematic home-based office set-ups, including poor postural habits that lead to musculoskeletal conditions, have been identified (Moretti et al, 2020;Sesenes et al, 2018). Psychosocial issues are also common, and include increased feelings of isolation, decreased work-life balance, loss of motivation, and increases in stress and anxiety (Bellmann & Hübler, 2020).…”
Section: Working From Homementioning
confidence: 99%
“…Many tasks in those kinds of workplaces require individuals to perform in poor working conditions to meet task demands, especially tasks that involve handling weights and pulling or pushing objects [5,6]. Repetitive back bending and twisting while handling weights can have a significant impact on postural stress [7,8]. Studies have reported that operators whose workplaces involve lifting, pulling, and pushing tasks are significantly more likely to suffer from lower back injuries compared to other kinds of workers without exposure to such handling tasks [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%